2007
DOI: 10.1111/j.1365-3024.2007.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant differences in GM allotype frequencies between two sympatric tribes with markedly differential susceptibility to malaria

Abstract: Fulani and Masaleit, sympatric tribes in eastern Sudan, are characterized by marked differences in susceptibility to Plasmodium falciparum malaria. To determine whether the two tribes differ in the frequency of immunoglobulin GM/KM allotypes, which are associated with immunity to several pathogens, serum samples from 50 Fulani and 50 age- and sex-matched Masaleit subjects were allotyped for several GM/KM determinants. The distribution of GM phenotypes as a whole, as well as a particular combination of KM and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…We found that the prevalences of the main GM and KM phenotypes differed according to the clinical presentation of malaria, and more precisely, we demonstrated the existence of an inverse relationship between the carriage of the GM 5,6,13,14; 1,17 phenotype and the presence of uncomplicated malaria [11]. An inverse observation was made by Pandey et al [5], who found a higher prevalence of this phenotype among the Masaleit tribe of Sudan, compared with the Fulani people, who had lower values of several malariometric variables. Fon people share closer genetic links with Masaleit people than with Fulani people, who are nomadic pastoralists with a Caucasoid genetic admixture.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…We found that the prevalences of the main GM and KM phenotypes differed according to the clinical presentation of malaria, and more precisely, we demonstrated the existence of an inverse relationship between the carriage of the GM 5,6,13,14; 1,17 phenotype and the presence of uncomplicated malaria [11]. An inverse observation was made by Pandey et al [5], who found a higher prevalence of this phenotype among the Masaleit tribe of Sudan, compared with the Fulani people, who had lower values of several malariometric variables. Fon people share closer genetic links with Masaleit people than with Fulani people, who are nomadic pastoralists with a Caucasoid genetic admixture.…”
supporting
confidence: 58%
“…Selection pressure exerted by pathogens helps maintain these loci polymorphisms because of associations between particular phenotypes and the quality of the immune response [2]. KM allotypes have been related to resistance and susceptibility to onchocerciasis [3], but few studies have investigated the potential relationships between GM and KM allotypes and Plasmodium falciparum malaria [4,5]. There is sufficient evidence to suggest that either plasmodial blood levels or malaria morbidity are under complex human genetic control and, thus, that genomic epidemiologic studies may help provide a complete description of these phenomena [6].…”
mentioning
confidence: 99%
“…This same phenotype was found to be more dominant in the Massalit, a tribe presumed to be more susceptible to malaria than Fulani [12]. The above-mentioned implication of GM 1,17 5,13,14,6 phenotype, might be due to the GM 6 allotype component.…”
Section: Discussionmentioning
confidence: 93%
“…The study showed that, the GM allelic combinations but not the KM allelic combinations had significant influence in uncomplicated malaria susceptibly and in the type and concentration of IgG isotype. While the implication of GM allotypes in susceptibility to bacterial infections and other diseases have been known for some time [20,21], the role of GM/KM polymorphisms in malaria susceptibility has only recently been investigated [12,22]. In this study, the GM 1,17 5,13,14,6 phenotype was significantly associated with increased susceptibility to malaria infections although paradoxically it was significantly associated with the highest baseline concentration of certain IgG and IgG isotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation